2013
DOI: 10.1016/j.jbi.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

A survey of SNOMED CT implementations

Abstract: The Systematised Nomenclature of Medicine Clinical Terms (SNOMED CT) has been designated as the recommended clinical reference terminology for use in clinical information systems around the world and is reported to be used in over 50 countries. However, there are still few implementation details. This study examined the implementation of SNOMED CT in terms of design, use and maintenance issues involved in 13 healthcare organisations across eight countries through a series of interviews with 14 individuals. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 20 publications
(22 reference statements)
0
80
0
1
Order By: Relevance
“…SNOMED CT is reportedly used in over 50 countries; however, there are still few articles that describe how this nomenclature is being used in operational settings [15]. Countries such as the United States of America, United Kingdom, Canada, Netherlands, New Zealand, and Australia have designated SNOMED CT as the recommended clinical reference terminology for clinical information systems [16]. The alternative to the use of equivalent nomenclature tables (synonyms) is the use of ontologies [17] which maintain data storage independent of content specification; but this approach is not yet standardized.…”
Section: Discussionmentioning
confidence: 99%
“…SNOMED CT is reportedly used in over 50 countries; however, there are still few articles that describe how this nomenclature is being used in operational settings [15]. Countries such as the United States of America, United Kingdom, Canada, Netherlands, New Zealand, and Australia have designated SNOMED CT as the recommended clinical reference terminology for clinical information systems [16]. The alternative to the use of equivalent nomenclature tables (synonyms) is the use of ontologies [17] which maintain data storage independent of content specification; but this approach is not yet standardized.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lee proposed that using post-coordinated expressions may be a convenient way to retrieve ICD codes but observed that such an approach is still untested [26]. We favored this approach to improve searches of MedDRA and agree that this methodology would be useful for other terminologies such as ICD.…”
Section: Perspectivesmentioning
confidence: 93%
“…SNOMED CT. SNOMED Clinical Terms is a large ontology of medical concepts that has been recommended as the reference terminology for clinical information systems in countries such as Australia, the United Kingdom, Canada, and the United States [11]. It includes formal definitions, codes, terms, and synonyms for more than 300,000 medical concepts.…”
Section: Domain-specific Vocabulariesmentioning
confidence: 99%